Analisis Konseptual dan Aplikatif I‘rab dalam Sintaksis Bahasa Arab: Studi Komparatif antara Teori Nahwu Klasik dan Pendekatan Linguistik Modern - Millatul Qudsiyah; Ainur Rofiq Sofa; Muhammad Sugianto (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to analyze i‘rab in Arabic syntax from two main perspectives: classical nahwu theory and modern linguistic approaches, as well as to evaluate the application of i‘rab in the construction of Arabic sentences. I‘rab refers to the inflection of a word’s ending, which indicates its syntactic function in a sentence, playing a crucial role in determining the meaning and structure of the sentence in Arabic. In the context of classical nahwu theory, as found in works such as Al-Kitab by Sibawaih and Al-Mufassal by Al-Zamakhsyari, i‘rab functions as a grammatical marker that helps to understand the relationships between the elements of a sentence, such as the subject, object, and complement. In contrast, modern linguistic approaches view i‘rab as one component in a more complex sentence structure, focusing on overall syntactic and semantic analysis. The research methodology employed is qualitative-descriptive with a content analysis approach, where data is collected from library studies covering primary literature in the fields of classical nahwu and modern linguistics. This study analyzes and compares the application of classical nahwu theory with modern linguistic approaches to i‘rab and its impact on understanding sentence structure in Arabic. The results show that although classical nahwu theory and modern linguistic approaches differ in their application of i‘rab, they complement each other in providing a more comprehensive understanding of Arabic sentence syntax. A proper understanding of i‘rab is essential not only in teaching Arabic but also in translating and interpreting Arabic texts, both in academic and practical contexts. This study is expected to contribute to the development of Arabic language teaching and serve as a reference for Arabic scholars interested in syntactic studies and its applications in Arabic sentence analysis.